PENGARUH PEMBERIAN KOMPOS SERASAH DAUN KARET TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis) STUM MINI - Timbul Hamonangan; Tengku Nurhidayah; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The research aims to study the effect and to obtain the best dose of rubber leaf litter compost on the growth of the rubber seedlings. The experiment has been conducted at the experimental farm of the Faculty of Agriculture, Riau University Pekanbaru from may to September 2018. The experimental unit was arranged in a Completely Randomized Design (RAL), consisting of 6 treatments: 0, 50, 100, 150, 200 and 250 g/seedling and replicated 3 times. Each experimental unit consisted of 3 seedlings. Parameters observed were seedling height,increase of stem diameter, number of leaves,length of leaf strands and leaf blade width. Data were analyzed statistically using analysis of variance and the mean of each treatment was compared with Duncan’s New Multiple Range Test at level 5 %. The result showed that the dose of rubber leaf litter compost at 250 g/seedling gave a better effect on enhacing the growth of rubber seedling. Keywords :Hevea brasiliensis, rubber leaf litter compost.